Optimization Emulgator Composition Of Water In Oil Emulsion Of Strawberry Fruits (Fragaria vesca L.) Based On Simplex Lattice Design Method - Dian Eka Ermawati (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Strawberry (Fragaria vesca L.) fruits contains nutrients that was beneficial to health because rich of antioxidant such as anthocyanin and flavonoids. Concentration of anthocyanins and flavonoids in strawberry during process would decline respectively 53% for pelargonidin3-O-glucoside and 40% for flavonoid. Water-oil emulsion consists of water and oil components were not mixed with each other, thus requiring emulgator to create a system that was homogeneous and stabilize the the antioxidants in strawberry.Emulgator that used in this study were : span 80, croduret 50 ss, and propylene glycol. They were optimized to know their combination in order to gain each portion of components which would produce an optimum formula of water/oil emulsion with good physical stability and stabilize the antioxidants ingredient. The optimization with Simplex Lattice Design method using Design Expert® software 7.1.5. Low limit and upper limit each components of emulgator were 1:1:1. The results of the responses of physical parameter were viscosity, separation ratio (F), and diameter of emulsion globule.Water/oil emulsion of strawberry that use emulgators : 2% Span80, 4% croduret 50 ss, and 2% propylene glycol produced a physically stable emulsion with the observation results had no significant difference to the prediction of Simplex Lattice Design. The observation results of viscosity value was -0.85 log P.as, 1.59 μm diameter of emulsion globule, and 0.99 cm of separation ratio (F). The prediction value were -0.56 log P.as of viscosity, diameter of emulsion globule of 3.26 μm and 0.97 cm of separation ratio (F). Strawberry fruits contains 23.3% of flavonoid, and 13.23% of anthocyanin. The optimum formula had 20% of flavonoids and 11.67% of anthocyanin. Combination of emulgator can stable the antioxidant compound of strawbbery fruits into water/oil emulsion formula. The consentration of antioxidant compounds decreased just ± 14% after formulation process.